Approaches to assessing the scientific and technological activities of scientific consortia in Russia and Europe - Philipp D. Belov (RUDN Journal of Economics)
The study presents a study of Russian and foreign approaches to assessing the scientific and technological activities of scientific consortia. Scientific consortia are collaborations of scientific and educational organizations popular in Russia and in the world that allow effectively solving multidisciplinary scientific problems and have a significant impact on the scientific and technological development of the country. In Russia, as in the world, there are state programs aimed at providing grants for the creation of scientific consortia. To assess the activities of scientific consortia, as well as to assess the effectiveness of using the allocated grants, various approaches are used in Russia and abroad. The study presents the experience of assessing the activities of Russian consortia created over the past 5 years within the framework of the national project “Science and Universities”. Such consortia include world-class research centers (WCRC), worldclass research and education centers (WСREC), and regional research and education centers (REC). In addition, foreign experience in assessing the activities of consortia and organizations carrying out scientific research in European countries is analyzed. The study examines the European system for assessing the scientific activities of educational organizations, the Research Excellence Framework (REF), which is largely based on an independent examination of the obtained scientific results, both applied and fundamental. In addition, the article examines approaches to assessing consortia created within the framework of the Horizon Europe program, a key EU program for funding research and innovation, the funding amount of which for the period 2021-2027 is 93.5 billion euros. The program promotes cooperation and enhances the impact of research and innovation on the development, support and implementation of EU policies in solving global problems. The study examines indicators characterizing the effectiveness of scientific activities of scientific consortia used in European countries and Russia. Comparative tables of indicators have been prepared, which compare the indicators used in the Russian Federation and in European countries. Based on the results of the study, the author proposes recommendations for improving approaches to assessing the scientific and technological activities of both scientific consortia in general and individual organizations - members of consortia in particular. Indicators used abroad to determine the efficiency of a consortium’s activities are proposed, which can be applied in Russian practice. The recommendations can be useful for government agencies and commercial structures when creating an international consortium based on organizations located in Russia and foreign countries (for example, the EAEU countries).